(3eHgeGJ GdCSGfjOs - (3CMeO Hf YHO GdQMje Hf GdMSjf GdcQOj GdYQGbj, CHh RQYI, hdj GdOjf , GHf GdYQGbj, J (B826 (3g` s ((3jhSa Hf jhSa Hf eMeO Hf NVQ Hf jYbhH Hf NVQ GdTGaYi s)
(3BNQgG (B:s
(3hGddg jYefG HWhdg hjQMefG HaVdg Hefg hcQeg hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B90 - (3U(B188s
(3dNUg ef cJH CHj eMeO YHO GdZfi Hf SYjO GdCROi hGdNWjH GdHZOGOi hGHf HTchGd hGHf WGgQ GdebOSi hCHi RcQjG Gdfhhis
(3hQJHg Ydi CHhGH Gdabgs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
(3LeY s
Keywords: (3GdJGQjNs